Problematika Penerapan Kurikulum Merdeka Dalam Pembelajaran Pendidikan Agama Islam (PAI) - Amali, Muhlas; Wulida Fajriyanti, Anzalina; Nuril Qulub , M. (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The aims of this research is to identify and analyze the challenges faced in applying the Merdeka Curriculum (Independent Curriculum) in Islamic Religious Education learning at MA Al-Ula Ambat Tlanakan Pamekasan. The method used in this research is qualitative approach with case studies, using in-depth interviews and observation as data collection techniques. The research results show that the implementation of the Independent Curriculum in madrasas faces several main challenges. One challenge is that freedom in teaching is not yet fully realized, even though the curriculum is designed to allow for more innovation in teaching methods.. Additionally, frequent changes in the curriculum create challenges in maintaining consistency and effectiveness of learning. Lack of adequate training for teachers is also a significant obstacle. Teachers need more support and coaching to be able to implement the Independent Curriculum well and according to its objectives. In the context of optimizing the Merdeka Curriculum (Independent Curriculum), interactive and adaptive approaches need to be enhanced to facilitate students' creativity and individual potential. Comprehensive support from all relevant parties, including local government, is essential to ensure the successful implementation of this curriculum. Apart from these challenges, students' cognitive difficulties and limited infrastructure also need further attention.